2015
DOI: 10.1096/fj.14-266247
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurement of energy substrate contribution to cold‐induced brown adipose tissue thermogenesis

Abstract: The present study was designed to investigate the effects of cold on brown adipose tissue (BAT) energy substrate utilization in vivo using the positron emission tomography tracers [(18)F]fluorodeoxyglucose (glucose uptake), 14(R,S)-[(18)F]fluoro-6-thia-heptadecanoic acid [nonesterified fatty acid (NEFA) uptake], and [(11)C]acetate (oxidative activity). The measurements were performed in rats adapted to 27°C, which were acutely subjected to cold (10°C) for 2 and 6 hours, and in rats chronically adapted to 10°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
221
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 189 publications
(238 citation statements)
references
References 58 publications
11
221
1
2
Order By: Relevance
“…Overall, we show that cold exposure induced fat browning and activated mitochondrial function; these results are consistent with previous studies (23)(24)(25). Therefore, we also suggest that BLC shows comparable effects to cold stimulation on fat browning.…”
Section: Blc Enhances Mitochondrial Function and Mitochondrial Biogensupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, we show that cold exposure induced fat browning and activated mitochondrial function; these results are consistent with previous studies (23)(24)(25). Therefore, we also suggest that BLC shows comparable effects to cold stimulation on fat browning.…”
Section: Blc Enhances Mitochondrial Function and Mitochondrial Biogensupporting
confidence: 93%
“…4D). Previous studies have shown that activated mitochondrial function can be induced by cold stress or b-adrenergic stimuli as well as by the expression of brown adipocyte-specific genes (23)(24)(25). Exposure of mice to cold temperatures in this study resulted in an ;15-fold increase in UCP1 mRNA levels and a significant increase in UCP1 protein levels in the scWAT of mice compared with mice at room temperature ( Supplementary Fig.…”
Section: Blc Enhances Mitochondrial Function and Mitochondrial Biogenmentioning
confidence: 52%
“…At the end of the 14 days of adaptation and before a 6-h fasting period (0600 -1200), mice were killed under isoflurane while blood was sampled in EDTA-coated tubes through intracardiac puncture 1 h following the CL injection. Plasma glucose, nonesterified fatty acid (NEFA), and triglyceride levels were measured as described previously (19), and insulin was measured by an ultrasensitive mouse insulin ELISA kit (no. 90080; Crystal Chem, Downers Grove, IL).…”
Section: Methodsmentioning
confidence: 99%
“…Chemical detection of the PCR products was achieved with SYBR Green (172-5271; Bio-Rad) on the CFX384 touch real-time PCR system (Bio-Rad, Mississauga, ON, Canada). Specificity of amplification was ensured using melt curve analyses followed by agarose gel electrophoresis of the amplified products, as described previously (19). Fold differences in target mRNA expression were calculated using the 2-delta cycle threshold method and ␤-microglobulin as the housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation